Alabama Veterans Rural Health Initiative: A Pilot Study of Enhanced Community Outreach in Rural Areas. Issue 2 (15th December 2013) - Hilgeman, Michelle M.; Mahaney‐Price, Ann F.; Stanton, Marietta P.; McNeal, Sandre F.; Pettey, Kristin M.; Tabb, Kroshona D.; Litaker, Mark S.; Parmelee, Patricia; Hamner, Karl; Martin, Michelle Y.; Hawn, Mary T.; Kertesz, Stefan G.; et al.
Abstract Purpose Access, enrollment, and engagement with primary and specialty health care services present significant challenges for rural populations worldwide. The Alabama Veterans Rural Health Initiative evaluated an innovative outreach intervention combining motivational interviewing, patient navigation, and health services education to promote utilization of the United States Veterans Administration Healthcare System (VA) by veterans who live in rural locations. Methods Community outreach workers completed the intervention and assessment, enrolling veterans from 31 counties in a southern state. A total 203 participants were randomized to either an enhanced enrollment and engagement outreach condition (EEE, n = 101) or an administrative outreach (AO, n = 102) condition. Findings EEE participants enrolled and attended VA appointments at higher rates and within fewer days than those who received AO. Eighty‐seven percent of EEE veterans attended an appointment within 6 months, compared to 58% of AO veterans (P < .0001). The median time to first appointment was 12 days for the EEE group and 98 days for the AO group (P < .0001). Additionally, a race by outreach group interaction emerged: black and white individuals benefited equally from the EEE intervention; however, black individuals who received AO took significantly longer to attend appointments than their white counterparts. Conclusions Results provide needed empirical support for a specific outreach intervention that speeds enrollment and engagement for rural individuals in VA services. Planned interventions to improve service utilization should ameliorate ambivalence about accessing health care in addition to addressing traditional systems or environmental‐level barriers.